Factors Related to Mothers' Habit in Making Breakfast for Their Children at MI Draul Hijrah Madani in Kupang - Rizki Fuji Maulidya; Ribka Limbu; Petrus Romeo (Universitas Nusa Cendana, 2022)
Breakfast contributes to improving nutritional and health status. Children who do not have breakfast in the morning will experience hypoglycemia or low blood sugar levels. This makes them weak, sleepy, and have difficulty concentrating. The habit of eating breakfast in children requires the participation of mothers in preparing breakfast for their children. This study aims to determine factors that are related to mothers’ habits of making breakfast for children at MI Darul Hijrah Madani in Kupang in 2020. It was an analytic observation using a cross-sectional design. The instrument used to collect data is a pre-prepared questionnaire. The population in this study was 215 mothers whose children study at MI Darul Hijrah Madani in Kupang. The sample was taken using simple random sampling to get 69 respondents. The results indicated that variables related to mothers’ habits of making breakfast for their children were knowledge (p=0.000<0.05) and attitude (p=0.001<0.05). On the other hand, variables that were not related to mothers’ habits in making breakfast for children were age (p=0.110>0.05), education (p=0.890>0.05), and occupation (p=0.176>0.05). Keywords: breakfast, mother's habit, students at elementary school